Deadly Decomposers: Distinguishing Life History Strategies on the Parasitism‐Saprotrophy Spectrum - Daniel C. G. Metz; Kelly L. Weinersmith; Alexis S. Beagle; Rudra M. Dixit; Christina G. Fragel; Clayton E. Cressler (Ecology Letters, 2025)
The ability to parasitize living hosts as well as decompose dead organic matter is both common and widespread across prokaryotic and eukaryotic taxa. These parasitic decomposers have long been considered merely accidental or facultative parasites. However, this is often untrue: in many cases, parasitism is integral to the ecology and evolution of these organisms. Combining life cycle information from the literature with a generalised eco‐evolutionary model, we define four distinct life history strategies followed by parasitic decomposers. Each strategy has a unique fitness expression, life cycle, ecological context, and set of evolutionary constraints. Correctly classifying parasitic decomposers is essential for understanding their ecology and epidemiology and directly impacts efforts to manage important medical and agricultural pathogens.

Delimiting the cryptic diversity and host preferences of Sycophila parasitoid wasps associated with oak galls using phylogenomic data - Yuanmeng M. Zhang; Sofia I. Sheikh; Anna K. G. Ward; Andrew A. Forbes; Kirsten M. Prior; Graham N. Stone; Michael W. Gates; Scott P. Egan; Linyi Zhang; Charles Davis; Kelly L. Weinersmith; George Melika; et al. (Molecular Ecology, 2022)
Cryptic species diversity is a major challenge regarding the species‐rich community of parasitoids attacking oak gall wasps due to a high degree of sexual dimorphism, morphological plasticity, small size and poorly known biology. As such, we know very little about the number of species present, nor the evolutionary forces responsible for generating this diversity. One hypothesis is that trait diversity in the gall wasps, including the morphology of the galls they induce, has evolved in response to selection imposed by the parasitoid community, with reciprocal selection driving diversification of the parasitoids. Using a rare, continental‐scale data set of Sycophila parasitoid wasps reared from 44 species of cynipid galls from 18 species of oak across the USA, we combined mitochondrial DNA barcodes, ultraconserved elements (UCEs), morphological and natural history data to delimit putative species. Using these results, we generate the first large‐scale assessment of ecological specialization and host association in this species‐rich group, with implications for evolutionary ecology and biocontrol. We find most Sycophila target specific subsets of available cynipid host galls with similar morphologies, and generally attack larger galls. Our results suggest that parasitoid wasps such as Sycophila have adaptations allowing them to exploit particular host trait combinations, while hosts with contrasting traits are resistant to attack. These findings support the tritrophic niche concept for the structuring of plant–herbivore–parasitoid communities.

Effects of turbidity and an invasive waterweed on predation by introduced largemouth bass - Maud C. O. Ferrari; Lynn Ranåker; Kelly L. Weinersmith; Matthew J. Young; Andrew Sih; J. Louise Conrad (Environmental Biology of Fishes, 2014)